Model Manajemen Koperasi Berbasis Komunitas untuk Pemberdayaan UMKM Rumahan - Intan Ratnasari; Dini Selasi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the management model of community-based cooperatives in empowering home-based MSMEs. Home-based MSMEs play a crucial role in improving the community's economy, but they still face various obstacles such as limited capital, suboptimal marketing, low managerial skills, and minimal use of digital technology. Community-based cooperatives offer an alternative solution through a participatory approach that emphasizes collaboration, member involvement, and strengthening the local economy. This study used a qualitative approach with descriptive methods. Data were collected through observation, interviews, and documentation involving cooperative administrators and home-based MSMEs. The results indicate that the community-based cooperative management model can increase members' business capacity by providing access to capital, entrepreneurship training, business mentoring, and collaborative product marketing. Furthermore, strong social ties among members are a crucial factor in building trust and maintaining the cooperative's sustainability. This study also found that digitalization and management innovation present both challenges and opportunities for cooperatives. Therefore, strengthening organizational governance, improving the quality of human resources, and utilizing digital technology need to be continuously developed to support the sustainable empowerment of home-based MSMEs.